(untitled) (Medico Legal Update, 2021)
Background: Abnormal sleep patterns are health challenge facing the Iraqi community and related to modernized behavioral changes. Aim of Study: To identify the prevalence of abnormal sleep patterns among overweight/obese adults in Baghdad city. Patients and Method: A descriptive cross sectional survey carried out in two Nutrition Clinics in Baghdad. During six months including 250 overweight/obese adults. The short sleep duration was defined as <7 hours/ day and late sleep onset was defined as sleeping at 11 o’clock pm and later. Results: Mean sleep duration was (7.23 hours). Sleep onset was in 66.8% of participants. Mean body mass index (BMI) was significantly higher in participants with short sleep duration (p<0.001). Short sleep duration was associated with younger age, male gender and negative medical history, while significant risk factors for late sleep onset are younger age, students and smoking. Conclusions: The prevalence of abnormal sleep patterns among overweight/obese was high. There is a strong link between short sleep duration and higher BMI.